Age-Related Changes in Nucleus Pulposus Mesenchymal Stem Cells: An In Vitro Study in Rats. (15th March 2017) - Zhao, Yachao; Jia, Zhiwei; Huang, Shanshan; Wu, Yaohong; Liu, Longgang; Lin, Linghan; Wang, Deli; He, Qing; Ruan, Dike
Abstract : The functions of mesenchymal stem cells (MSCs) appear to decline with age due to cellular senescence, which could reduce the efficacy of MSCs-based therapies. Recently, MSCs have been identified in the nucleus pulposus, which offers great potential for intervertebral disc (IVD) repair. However, this potential might be affected by the senescence of nucleus pulposus MSCs (NPMSCs), but whether or not this exists remains unknown. The aim of this study was to investigate the age-related changes in NPMSCs. NPMSCs isolated from young (3-month-old) and old (14-month-old) Sprague-Dawley rats were cultured in vitro. Differences in morphology, proliferation, colony formation, multilineage differentiation, cell cycle, and expression of β -galactosidase (SA- β -gal) and senescent markers (p53, p21, and p16) were compared between groups. Both young and old NPMSCs fulfilled the criteria for definition as MSCs. Moreover, young NPMSCs presented better proliferation, colony-forming, and multilineage differentiation capacities than old NPMSCs. Old NPMSCs displayed senescent features, including significantly increased G0/G1 phase arrest, increased SA- β -gal expression, decreased S phase entry, and significant p53-p21-pRB pathway activation. Therefore, this is the first study demonstrating that senescent NPMSCs accumulate in IVD with age. The efficacy of NPMSCs is compromised by donor age, which should be taken into consideration prior to clinical application.